Implementasi SAP Plant Maintenance dalam Strategi Predictive Maintenance untuk Efisiensi Biaya dan Optimalisasi Kinerja Aset - Prayoga, Ibra Agus; Raharjo , Raden Johnny Hadi (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
The implementation of predictive maintenance supported by SAP Plant Maintenance (SAP PM) at PT Xyz has proven to be effective in reducing machine downtime, lowering maintenance costs, and improving asset reliability. The integration of SAP PM with Industry 4.0 technologies such as IoT sensors, AI-based analytics, and real-time notification systems strengthens operational efficiency and ensures continuous performance. Empirical results show improvements in key performance indicators, including a 20-25% reduction in downtime, a 30% reduction in maintenance costs, an increase in asset availability to 97%, an MTBF extension of up to 511 hours, and an OEE rate of 92.1%. These findings highlight the strategic role of digital predictive maintenance in increasing competitiveness and supporting long-term sustainability in manufacturing operations.